Analysis of the Potential Comparative Advantage of the Plantation Sector in Pidie Jaya Regency Using the LQ Method - Miswardi Miswardi; M. Rasyidin; M. Saleh (Electronic Journal of Education, Social Economics and Technology, 2025)
Regional economic growth is greatly influenced by leading sectors. In Pidie Jaya Regency, the plantation sector shows significant potential as a foundation of the local economy due to agro-climatic conditions that favor crops such as oil palm, cocoa, and areca nut. Analyzing the sector's comparative advantage is crucial for formulating sustainable and data-driven development strategies. This study employs a quantitative approach using the Location Quotient (LQ) method to assess the comparative advantage of the plantation sector. Secondary data on the GRDP (Gross Regional Domestic Product) of the sector from 2016 to 2024 were analyzed using the LQ formula, comparing regional output with national figures, while also examining growth trends and fluctuations over the period. The results show that the LQ value for the plantation sector in Pidie Jaya remained below 1 throughout the study period, although it exhibited an upward trend. External factors such as the COVID-19 pandemic affected the sector’s performance; however, the growth trend indicates further development potential. Additionally, regional GRDP demonstrated stable growth, reflecting the resilience of the local economy.